Focus on the Predictive Value of Subclassification of Extratumoral Structural Abnormalities for Malignant Nonspiculate and Noncalcified Masses on Digital Mammography - Xu, Ye; Sun, Jianghong; Guo, Fei; Nanding, Abiyasi; Li, Qiyang; Jiang, Dan (Frontiers in Genetics, 2022)
Purpose: To determine the independent risk factors associated with malignant nonspiculate and noncalcified masses (NSNCM) and evaluate the predictive values of extratumoral structural abnormalities on digital mammography. Methods: A total of 435 patients were included between January and May 2018. Tumor signs included shape, density and margin, which were evaluated. Extratumoral signs were classified into extratumoral structural abnormalities (parenchymal and trabecular) and halo, subclassification included contraction, distortion, pushing and atrophy sign of parenchyma, parallel, vertical and reticular trabecula sign, narrow and wide halo. Univariate and multivariate analysis were performed. Positive predictive value (PPV) of independent predictor was calculated, and diagnostic performance was evaluated by the receiver operating characteristic curve. Results: Of all cases, 243 (55.8%) were benign and 192 (44.2%) were malignant. Extratumoral contraction sign of parenchyma was the strongest independent predictor of malignancy (odds ratio [OR] 36.2, p < 0.001; PPV = 96.6%), followed by parenchymal distortion sign (OR 10.2, p < 0.001; PPV = 92%), parallel trabecula sign (OR 7.2, p < .001; PPV = 85.6%), and indistinct margin of tumor (OR 4.3, p < .001; PPV =70.9%), also parenchymal atrophy sign, wide halo, vertical trabecula, age ≥ 47.5 years, irregular shape and size ≥ 22.5 mm of tumor (OR range, 1.3-4.0; PPV range, 56.6-83.6% ). The diagnostic performance of most of extratumoral signs was between that of indistinct margin and irregular shape of tumor. Conclusion: The subclassification of extratumoral structural abnormalities have important predictive value for mammographic malignant NSNCM, which should be given more attention.